Fatwa On Waqf: Specialized Analysis In Hand Over Of Waqf Lands by State Authority - Mohd Afandi Bin Mat Rani (UIN Sunan Gunung Djati Bandung, 2015)
This paper tries to analyze the fatwa regarding issues of hand over of waqf lands to the State Authorities which have been going on since the year 1951 to 2006. Though it may only focus on several states in Malaysia, such revelations can act as strong exemplary of the current and overall fatwa that has been issued by the authorized party. This is due to the idea that the approaches and development of fatwa are very much similar to each other. However, fatwa regarding the law of hand over of waqf lands by the government are rarely discussed and are often decided by the State Fatwa Committee as well as the National Fatwa Committee. Despite the hand over as an intention for country’s development, the procedures in dealing with this issue are not correctly applied as approved by the Mufti nor is it referred to Islamic State Council or ‘Majlis Agama Islam Negeri’ (MAIN), including the waqf lands entrusted to the Muslim community. This could be the effect of Land Acquisition Act 1960 which stood out more than its counterpart; MAIN, though the latter being the only authorized endowment trustee in Malaysia. This paper addresses various issues on constraints of waqf procedures and suggestions in improving its effectiveness.